A 3D model of three phase shunt reactors by using a finite element technique with coupling to global quantities - Hung Bui Duc; Tu Pham Minh; Bao Doan Thanh; Duc-Quang Nguyen; Vuong Dang Quoc (Institute of Advanced Engineering and Science, 2023)
The finite element technique is used widely for researchers and manufacturers to design and simulate electrical systems in general and electrical machines such as shunt reactors (SRs) and transformers in particular. Many papers have recently applied several methods to analyze magnetic fields, copper losses and joule power losses in the shunt reactors (SRs). In this research, the finite element technique with coupling to global quantities is proposed to investigate the voltage and current distributions in the windings, and compute the distribution of magnetic field in the air gap and along the air core of the SR, as well as copper and core losses. The developed method is directly applied to the practical SR of 91 MVAr and a rated voltage of 500 kV. The finite element method (FEM)-simulated results are validated with experimental results to ensure accuracy and reliability. This facilitate designing the reactor.